The THE ROLE OF PRONUNCIATION IN FOREIGN LANGUAGE LEARNING: STUDENTS PERSPECTIVES AT MAN PEMATANG SIANTAR - Bahagia Saragih; Dinda Putri Adila; Kayla Khairunnisa Adhy Saputra; Rahmi Syahidah Azzam; Zaskia Safira; Dinda Saharani Harahap; Nazwa Ghaisyah Azzahra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to explore the perceptions and attitudes of 11th-grade science students at MAN Pematang Siantar regarding the importance of pronunciation in English language learning. Using a descriptive quantitative method with a questionnaire as the main instrument, the study involved 34 participants who were analyzed based on four main indicators: perception of importance, technical challenges, self-study strategies, and the teacher's role in the classroom. The results of the study showed a very high level of awareness among students, with the majority acknowledging that correct pronunciation is the key to effective communication and a major factor in boosting confidence. Nevertheless, technical challenges still exist, particularly related to the inconsistency between written spelling and the way words are pronounced in English. The findings also revealed a high level of student independence in utilizing digital technology as well as a strong desire to receive direct feedback from the teacher.